THE EFFECT OF CURING METHODS ON THE PROPERTIES OF HIGH PERFORMANCE LIGHTWEIGHT CONCRETE IN HOT DRY WEATHER CONDITIONS - Khaled Ahmed, Hisham; Ismail Khalil, Wasan; Hadi Jumaa, Nada (Journal of Engineering and Sustainable Development, 2017)
This study is concerned with the effect of curing methods and early curing on the some properties of high performance lightweight concrete HPLWC that exposed to effects of hot dry weather conditions to improve the performance of concrete structures. The experimental work was carried out during Iraqi summer season at 12:00 pm. with average temperature 55°C and relative humidity RH 13% under actual atmospheric condition by used fixed mix proportions for preparing and casting specimens and applying different curing methods represented by water curing (WC) for 13 day, water based curing compound (WBC), and bitumen based curing compound (BBC), as well as curing specimens by burlap covering with sprinkling water 3 times a day(BWS) after (5:00, and 8:00,24:00)h. from casting for 13 day, and air curing(AC). The effect of selected curing methods on the properties of HPLWC was evaluated by measuring compressive and splitting tensile strength, modulus of rupture, static and dynamic modulus of elasticity and pulse velocity. The results show that the best performance with regard to the 28 day strength and later ages was in specimens cured by applying WBC followed WC, and then BWS, and less order BBC and in the decreasing order specimens of AC. The results display that early curing after (5:00, and 8:00) h. from casting does not improve concrete properties comparative to that cured after 24 h.